2005
DOI: 10.1002/eji.200535243
|View full text |Cite
|
Sign up to set email alerts
|

CD56brightCD16 NK cells accumulate in psoriatic skin in response to CXCL10 and CCL5 and exacerbate skin inflammation

Abstract: Psoriasis is an immune-mediated skin disease characterized by lymphocytic infiltration and altered keratinocyte differentiation. Using immunohistochemical techniques we found that the cellular infiltrate in acute psoriatic plaques includes 5-8% CD3 -CD56 + natural killer (NK) cells, mostly localized in the mid and papillary dermis. NK lymphocytes isolated from punch biopsy specimens of psoriatic plaques showed a CD56 bright CD16 -CD158b -phenotype, failed to express the skin homing cutaneous lymphocyte-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
211
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(223 citation statements)
references
References 62 publications
11
211
0
1
Order By: Relevance
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
Section: Dc-dependent Nk-cell Recruitment Is Ccr5 Mediatedmentioning
confidence: 73%
See 2 more Smart Citations
“…DC maturation induced by IFN-g/FMKp led to an enhanced (41.5-fold increase in chemiluminescence) secretion of eleven chemokines as compared with TNF-a/PGE2-induced maturation. These chemokines included CCL5, CXCL10 and CCL19 to which NK cells can respond [23][24][25]. Quantification with ELISA confirmed that these chemokines were indeed produced by IFN-g/FMKp-matured DC and not by TNF-a/PGE2-matured DC (Fig.…”
Section: Dc-dependent Nk-cell Recruitment Is Ccr5 Mediatedmentioning
confidence: 73%
“…However, during inflammation, it has been demonstrated that NK cells are able to migrate into inflamed tissue and draining lymph nodes [7,23]. Currently, it remains unclear what drives human NK-cell migration in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of CD56 bright are probably end-stage effector cells with an important role in restricting infections through monokine-induced cytokine production that guide the adaptive immune response [6]. Indeed, viral infections strongly impact the composition of the pool of CD56 bright [39][40][41] that can be found at inflammatory sites in contact with APC in a wide variety of inflammatory diseases [6,42,43].NK cells after HSCT express high levels of CD56 [27-30, 32, 33]. This has often been used as an argument that ptCD56 bright are immature [29,31,32,34].…”
mentioning
confidence: 99%
“…In mice, recruitment of NK cells to LNs depends on CD62L and CXCR3 [32]. Furthermore, CCR1 [33], CCR5 [34,35], CCR7 [36], CXCR1 [37], CX 3 CR1 [38], LPAM-1 (a4b7 integrin) [39], and CD103 (aEb7 integrin) [40] have also been implicated in recruitment of NK cells to sites of inflammation. Surprisingly, NK cells in HIV 1 individuals exhibited reduced CX 3 CR1 (po0.01) and CXCR1 (po0.01) expression compared with uninfected controls, suggesting that despite HIV-associated inflammation, NK cells may have a reduced capacity to migrate to the LN due to reduced expression of chemokine receptors that are critical for homing to lymphoid tissues and sites of inflammation (Fig.…”
Section: Nk Cells May Affect Their Recruitment To Lnmentioning
confidence: 99%